(untitled) - Fee, Gordon D.; (1934-...) (U.S.A, 1982)
Understanding the Bible isn$1 (Bt for the few, the gifted, the scholarly. The Bible is accessible. It$1 (Bs meant to be read and comprehended by everyone from armchair readers to seminary students. A few essential insights into the Bible can clear up a lot of misconceptions and help you grasp the meaning of Scripture and its application to your twenty-first-century life. More than three quarters of a million people have turned to (3z(BHow to Read the Bible for All Its Worth(3y (Bto inform their reading of the Bible.s
Keywords: Bible -- Study and Teaching